A review on subcutaneous veins localization using imaging techniques - Shahzad, A. (Bentham Science Publishers B.V., 2014)
In daily medical practices intravenous (IV) catheterization is performed on the majority of patients to inject medication or to get blood samples. Patients whose veins are not visible require multiple attempts in order to insert the catheter accurately. Different techniques have been proposed and a few are in use at present to localize the veins in order to avoid the wrong catheterization and reduce the number of attempts. In literature, numerous imaging techniques can be found for subcutaneous veins localization. These techniques have dissimilar methods and applications. The aim of this paper is to present a review on the most commonly used techniques amongst all of them; these are Transillumination, Photoacoustic and near infrared (NIR) imaging. The basic working principle along with evolution of these techniques has been stated from the current state-of-the-art. Advantages and limitations are underlined in terms of effectiveness, simplicity in usage, portability and cost effectiveness. Â© 2014 Bentham Science Publishers.